92.9k views
4 votes
4(x-5)² + 12(x-5)



please help me out i am so confused​

1 Answer

3 votes

Answer:

The simplified expression is:

= 4(x-5)(x-2)

Explanation:

Given that:

=4(x-5)² + 12(x-5)

By simplifying we get

= 4(x^2 -10x + 25) + 12x - 60

= 4x^2 - 40x + 100 + 12x - 60

Adding like terms:

= 4x^2 -28x + 40

=4(x^2-7x+10)

=4(x^2-2x-5x+10)

=4(x(x-2)-5(x-2))

By taking common we get:

= 4(x-5)(x-2)

This is the simplified expression.

I hope it will help you!

User James Soubry
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.